Influence of Dialysis on the Glucose Profile in Patients with Diabetes: Usefulness of Continuous Glucose Monitoring - Chantrel, F.; Sissoko, H.; Képénékian, L.; Smagala, A.; Meyer, L.; Imhoff, O.; Serb, L.; Fleury, D.; Dorey, F.; Krummel, T.; Le Floch, J. P.; Kessler, L. (Hormone and Metabolic Research, 2014)
We sought to investigate the impact of dialysis on glucose profiles of diabetic patients using continuous glucose monitoring (CGM). The study included 33 hemodialyzed patients with diabetes (14 females and 19 males; mean age: 66±8 years; patients with type 2 diabetes: 30; mean duration of dialysis: 3.8±2.6 years) who were under insulin treatment. After a run-in period, CGM was performed for 48 h, including a dialysis session. Three CGM sessions were proposed for each patient over a 3-month period. CGM results were analyzed during and after dialysis at 6 different time points. Moreover, data were analyzed in 7 different day periods according to meals. Of the 99 CGM available, 21 were excluded because of technical issues or patient refusal. The CGM results indicated that mean glucose values (7.5±2.5 mmol/l vs. 9.4±1.9 mmol/l; p<0.001) and variability indices (p<0.001) were lower, whereas the frequency of hypoglycemia (4.4±9.6% vs. 2.1±7.9%; p<0.001) was higher during hemodialysis sessions. Significant differences were observed in glucose values only before and 2 h after breakfast (p<0.001). Compared with other day periods, glucose values were lower during the second half of the night and higher before and after dinner (p<0.001). In summary, CGM allows the identification of a particular glucose profile in hemodialyzed diabetic patients. CGM seems feasible and clinically useful for the analysis of glucose profiles in this group of patients.
Keywords: diabetes; hemodialysis; continuous glucose monitoring